Philippine bats of the genus Kerivoula (Chiroptera: Vespertilionidae): Overview and assessment of variation in K. pellucida and K. whiteheadi - Sedlock, Jodi L.; Heaney, Lawrence R.; Balete, Danilo S.; Ruedi, Manuel (Zootaxa, 2020)
Bats of the genus Kerivoula (Mammalia, Chiroptera) are widespread in the Philippines with four reported species, but have been poorly known due to a paucity of specimens. We provide the first molecular phylogeny for Philippine Kerivoula, which supports the existence of four distinct clades that we treat as species (K. hardwickii, K. papillosa, K. pellucida, and K. whiteheadi); these four overlap broadly geographically. Each of these may be recognized on the basis of cytochrome b sequences and external and craniodental morphology. Detailed examination of K. pellucida shows little geographic differentiation within the Philippines, but they differ subtly from those on the Sunda Shelf. We consider K. whiteheadi to be composed of four recognizable clades, each restricted to a geographic region within the Philippines. We consider K. bicolor, from peninsular Thailand, and K. pusilla, from Borneo, to be distinct from K. whiteheadi. Our data indicate the presence of two species within the Philippines currently lumped as K. hardwickii; further study of these is needed. A calibrated phylogeny suggests that Kerivoula began arriving in the Philippines about 10 MYA, with each of the four current lineages arriving independently.